Analisis Faktor-Faktor yang Mempengaruhi Sikap Sosial dalam Bergaul pada Peserta Didik Kelas IX SMP Islam Nurul Ihsan Siantan Hilir Kota Pontianak - Soraya, Ayu; Aminuyati, Aminuyati; Hafizi, M. Zainul; Okianna, Okianna; Utami, Patrisia Rahayu (Indo-MathEdu Intellectuals Journal, 2025)
Adolescence is an important developmental stage where individuals begin to form their social identity, which is influenced by various surrounding environments. This research aims to analyze the factors that influence social attitudes in socializing among class IX students at Nurul Ihsan Islamic Middle School, Siantan Hilir, Pontianak City. This research uses a qualitative approach with data collection techniques through observation, interviews and documentation. The data analysis techniques usd are data collection, data reduction, and data presentation. The research results show that students' social attitudes are formed from the interaction of various factors, namely the family environment (parenting patterns, communication, harmony), school (relationships with teachers and friends, extracurricular activities, social climate), society (social norms and social involvement), and social media (duration of use and type of content). The dominant social attitudes shown by students include empathy, cooperation, tolerance and respect. However, behavior was also found that did not support social interaction, such as impoliteness, difficulty adapting, and minimal social participation. This research emphasizes the importance of collaboration between family, school and community in forming positive social attitudes in adolescents. These findings are contextual and cannot be widely generalized due to the limited number of informants and the research location being limited to one school.